Pengaruh Proses Post Weld Heat Treatment (PWHT) terhadap Sifat Fisik dan Mekanik Sambungan Las Tungsten Inert Gas (TIG) pada Baja SS 400 - Yustiasih Purwaningrum; Reza Arief Sidiq; Isal Alvianto (TURBO [Tulisan Riset Berbasis Online], 2026)
The aimed of this research is to find the PWHT (post weld heat treatment) temperature that can produce the optimal physical and mechanical properties of TIG (tungsten inert gas) welded joints on SS 400 steel.. The PWHT temperature in previous TIG welding studies on steel used temperatures below 700℃. At this temperature, the steel's microstructure consists of ferrite and pearlite, so the microstructure after PWHT cooling does not change, remaining ferrite and pearlite. The PWHT process used in this study is quenching with water as the cooling medium. The temperature variations used are 900℃, 1000℃, and 1100℃. Within this temperature range, the steel's pearlite phase has transformed into austenite. After cooling, the austenite phase will change depending on the cooling rate, which further increases the potential improvement in its mechanical properties. The material used is SS 400 steel with dimensions of 300 mm x 100 mm and a thickness of 5 mm. The TIG welding process was carried out using a tungsten electrode AWS A5 12-80 ϕ 2.4 mm and filler metal ER 70S-6 ϕ 1.6 mm. The welding parameters used were a voltage of 230 V, current of 95 A, welding speed of 1.46 mm/s, and argon shielding gas. The tests conducted were dye penetrant testing, microstructure observation, tensile testing, bending testing, microvickers hardness testing, and corrosion rate testing. The test results indicate that a PWHT temperature variation of 1000℃ produces the most optimal weld joint. The tensile strength of the weld with a temperature variation of 1000℃ is 246.31 MPa. This value is 25.8% higher compared to the 900℃ variation and 9.9% higher compared to the 1100℃ variation. The bending test results show that the bending strength of the weld with PWHT at 1000℃ is 483.99 MPa. This value is higher compared to the welds with PWHT at 900℃ and 1100℃, which have bending strengths of 307.52 MPa and 280.81 MPa, respectively. The microstructure formed after the PWHT process at all temperature variations is the same, which is martensite with hard and brittle properties, due to the rapid cooling process. The corrosion rate values fall into the good category for all welds with PWHT. This research produced PWHT temperature data that is useful for improving the physical and mechanical properties of TIG welding results on SS 400 steel, which can be applied in the construction field.